The Analyses of Learning Strategies in English as a Second Language: Theoretical Classification and Measurement Test - Asti Gumartifa; Indah Windra Dwie Agustiani (VELES Voices of English Language Education Society, 2020)
Learning acquisition concerns the process of the learning situation, where the processes are signs, grammatical constructions, and stimulates cognitive. It is very beneficial for both teachers and learners to support learning in the classroom. Teachers’ and learners’ understanding to the importance of learning strategies must be balance. It means both teachers and learners should know some positive impact of learning strategies used. When learners and teachers have a good awareness of the implementation of learning strategies used in the learning process they will find the enjoyment of learning and teaching in the further. Therefore the teacher must explicitly introduce and ask learners to use learning strategies consciously and continually. The purpose of this research is to mention some overviews of Learning Strategies of Inventory for Language Learning (SILL) version 5.0. Learning strategies classified into direct and indirect strategies, where direct strategies process focus on memory, cognitive, and compensation, then indirect strategies emphasized in metacognitive, affective, and social affective.